1991
DOI: 10.1007/bf00194863
|View full text |Cite
|
Sign up to set email alerts
|

Counter jet stagnation flows

Abstract: The present paper concerns the stagnation flow produced by counter flowing air jets. Little experimental information exists on such flows in spite of their extensive employment in the theoretical treatment of diffusion flames. To remedy this situation, laserDoppler measurements were performed to quantify the entire flow field. The experiments are described and the results of the velocity measurements presented. Differences between the investigated flow field and the ideal flow field, employed in theoretical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 10 publications
4
60
0
Order By: Relevance
“…As pointed out by Rolon et. al [33], the 2U air /H approximation only converges on the measured -1/2 axial and radial SRs well beyond H/D > 1, or preferably at > 1.5. In our subsequent analysis of published n-heptane/N 2 -air extinction data, derived from a 22 mm matrix burner [36], we applied the above correction factor of 0.42 to allow a SR data comparison (discussed later).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…As pointed out by Rolon et. al [33], the 2U air /H approximation only converges on the measured -1/2 axial and radial SRs well beyond H/D > 1, or preferably at > 1.5. In our subsequent analysis of published n-heptane/N 2 -air extinction data, derived from a 22 mm matrix burner [36], we applied the above correction factor of 0.42 to allow a SR data comparison (discussed later).…”
Section: Resultsmentioning
confidence: 89%
“…Finally, (9) a comprehensive "Idealized Flameholding Scale" will be shown that includes all the results discussed above, extends a factor of 50 to pure H 2 , and includes the effects of HC reactivity with H-atoms. [33]. Both the measured radial SR, and -1/2 the measured axial SR, are shown as a function of nozzle separation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This configuration is briefly described in the next paragraph. More information of the burner can be found in [2,3].…”
Section: Counterflow Burner Devicementioning
confidence: 99%
“…25 As a result, derived absolute strain rates can be compared directly with extinction limits determined numerically using either a 1-D, or preferably 2 -D, Navier Stokes simulations with detailed transport rates and finite rate kinetics. Initially, numerical extinction results for me thane, 23 based on relatively well-validated chemical kinetics, agreed quite closely (within < 10%) with the absolute strain rate scale.…”
mentioning
confidence: 99%